Moderating Role of Organizational Based Self Esteem and Relationship between Transformational Leadership and Creativity - Zennouche Mohamed (Journal of Management Practices, Humanities and Social Sciences, 2024)
Based on the in-depth and systematic research of organizational-based self-esteem (OBSE) theoretical literature, this paper makes a sort of main research issues such as the connotation, measurement method, antecedents and results, and moderating effect of OBSE, to clarify the research status of organizationally based self-esteem (OBSE) theory. The study aimed to investigate the moderating role of organizational-based self-esteem OBSE between transformational leadership and creativity, as well as to investigate the effect of transformational leadership on creativity. A total of 172 employees took part in the survey, and 165 of those responses were legitimate for the exam. The findings indicate that organization-based self-esteem moderates the association between transformational leadership and creativity, as indicated by hierarchical regression analysis. The findings also demonstrate that transformational leadership significantly and favourably influences creativity. The study's findings emphasize the value of transformational leadership, creativity, and organizational-based self-esteem. According to the study, in order to retain employee efficiency, human resources management should develop practices that will increase trust and self-esteem based on organizational principles. It should also improve the relationship between the organization and its workforce in order to achieve a high level of creativity. The further research trend of the theory and the preliminary discussion on the management of organizational-based self-esteem (OBSE) of employees.